Skeletal muscle myopenia in mice model of bile duct ligation and carbon tetrachloride‐induced liver cirrhosis - Giusto, Michela; Barberi, Laura; Di Sario, Francesca; Rizzuto, Emanuele; Nicoletti, Carmine; Ascenzi, Francesca; Renzi, Anastasia; Caporaso, Nicola; D'Argenio, Giuseppe; Gaudio, Eugenio; Musarò, Antonio; Merli, Manuela (Physiological reports, 2017)
Skeletal muscle myopathy is universal in cirrhotic patients, however, little is known about the main mechanisms involved. The study aims to investigate skeletal muscle morphological, histological, and functional modifications in experimental models of cirrhosis and the principal molecular pathways responsible for skeletal muscle myopathy. Cirrhosis was induced by bile duct ligation (BDL) and carbon tetrachloride (CCl4) administration in mice. Control animals (CTR) underwent bile duct exposure or vehicle administration only. At sacrifice, peripheral muscles were dissected and weighed. Contractile properties of extensor digitorum longus (EDL) were studied in vitro. Muscle samples were used for histological and molecular analysis. Quadriceps muscle histology revealed a significant reduction in cross‐sectional area of muscle and muscle fibers in cirrhotic mice with respect to CTR. Kinetic properties of EDL in both BDL and CCl4 were reduced with respect to CTR; BDL mice also showed a reduction in muscle force and a decrease in the resistance to fatigue. Increase in myostatin expression associated with a decrease in AKT‐mTOR expressions was observed in BDL mice, together with an increase in LC3 protein levels. Upregulation of the proinflammatory citochines TNF‐a and IL6 and an increased expression of NF‐kB and MuRF‐1 were observed in CCl4 mice. In conclusion, skeletal muscle myopenia was present in experimental models of BDL and CCl4‐induced cirrhosis. Moreover, reduction in protein synthesis and activation of protein degradation were the main mechanisms responsible for myopenia in BDL mice, while activation of ubiquitin‐pathway through inflammatory cytokines seems to be the main potential mechanism involved in CCl4 mice. The study elucidates the main morphological and functional alterations involved in skeletal muscle mass in experimental models of cirrhosis secondary to bile duct ligation (BDL) and CCl4 administration. A different molecular pathway seems to be activated in response to liver damage in the two models of liver cirrhosis leading to myopenia. Both models have the potential to be applied in basic research to better clarify molecular pathways responsible for skeletal muscle myopenia in liver cirrhosis.